Hubungan Aktivitas Fisik Terhadap Kejadian Sindrom Metabolik Pada Civitas Akademika Universitas Nusa Cendana - Jannah, Ike Nur Safitri Miftahul; Buntoro, Ika Febianti; Folamauk, Conrad Liab Hendricson; Kareri, Dyah Gita Rambu (Cendana Medical Journal, 2023)
Background: Metabolic syndrome is a condition in which the formation of a group of metabolic dysregulations occurs, namely insulin resistance, atherogenicdyslipidemia, central obesity, and hypertension. The imbalance between calorieintake and calorie use will result in obesity, where obesity is a major component ofmetabolic syndrome. Physical activity is one of the factors causing metabolic syndrome. Aim: Analyzing the relationship of physical activity to the incidence of metabolicsyndrome in the academic community of Nusa Cendana University. Method: This research method is correlation analytics with Cross Sectional design,which is research used to analyze the relationship between dependent andindependent variables with data collection carried out simultaneously at one time. In this study, data analysis for physical activity was carried out by filling out the GPAQ (Global Physical Activity Questionnaire) questionnaire and for thediagnosis of metabolic syndrome based on the criteria of the Adult Treatment Panel(ATP) III. using Phi Cramer's V test with the variable level of the Bivariate testP<0.05. Results: The test results using the Phi Cramer's V statistical test obtained that therewas no association of physical activity and metabolic syndrome with p = 0.850(p<0.05). Conclusion: There is no significant relationship between physical activity and theincidence of metabolic syndrome in the academic community of Nusa Cendana University. Keywords: Metabolic syndrome; physical activity;